2018
DOI: 10.3153/fh18019
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Rheological and Structural Characteristics of Alcohol Precipitated Fraction of Gum Tragacanth

Abstract: Obtaining specific polysaccharide of gum by separating other parts appears to be an approach to get a hydrocolloid with a higher quality and new functional properties. Therefore, gum tragacanth (GT) was used for these aims. The characterization of alcohol precipitated part of GT were performed in terms of physico-chemical compositions (moisture, ash, protein, color and transparency); rheological behaviors aqueous solutions at different concentration, temperature, pH, presence of salt and sucrose; and structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Figure 4 shows the FTIR analysis of chemical functional groups of GT powder and PVA, PVA/GT, and PVA/GT/CNC films. The FTIR spectra for GT powder with an absorption band at 2149 cm −1 corresponded to various carbonyl groups in the gum while peaks of carbonyl stretching in aldehydes, ketones, and carboxylic acids were presented at 1750 cm −1 [ 70 ]. The bands at 1635 cm −1 and 1442 cm −1 were attributed to asymmetrical and symmetrical stretching of carboxylate groups, respectively, while peaks at 1242 cm −1 and 1020 cm −1 displayed C-O stretching vibration in polyols and alcoholic groups, respectively [ 22 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 shows the FTIR analysis of chemical functional groups of GT powder and PVA, PVA/GT, and PVA/GT/CNC films. The FTIR spectra for GT powder with an absorption band at 2149 cm −1 corresponded to various carbonyl groups in the gum while peaks of carbonyl stretching in aldehydes, ketones, and carboxylic acids were presented at 1750 cm −1 [ 70 ]. The bands at 1635 cm −1 and 1442 cm −1 were attributed to asymmetrical and symmetrical stretching of carboxylate groups, respectively, while peaks at 1242 cm −1 and 1020 cm −1 displayed C-O stretching vibration in polyols and alcoholic groups, respectively [ 22 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous studies have reported an extremely wide endothermic range with a peak at about 130°C for the gum tragacanth, with the starting temperature ( T onset ) of this range in some studies being as high as 25°C and some 50°C, and with a T endset of about 220°C 11,13 . The reason for this wide temperature range, which is related to the residual water outflow from the heterogeneous structure of the gum, is the presence of numerous hydrophilic functional groups and the capability of the bassorin part of the gum to retain water 44 . Ultimately, this mechanism prevents sudden melting behavior in this polysaccharide 13…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 shows the FTIR analysis of chemical functional groups of GT powder, PVA, PVA/GT and PVA/GT/CNC lms. The FTIR spectra for GT powder with an absorption band at 2149 cm −1 corresponded to various carbonyl groups in the gum while peaks of carbonyl stretching in aldehydes, ketones and carboxylic acids were presented at 1750 cm −1 (Kurt, 2018). The bands at 1635 cm −1 and 1442 cm −1 were attributed to asymmetrical and symmetrical stretching of carboxylate groups, respectively, while peaks at 1242 cm −1 and 1020 cm Swelling of wound dressing is an important factor that relates to wound exudates absorption and prevention of infection and can be explained by physical and chemical changes in material structure that help water molecules to diffuse internally, leading to an increase in free volume (Jahan et al, 2018;Kumar et al, 2014;Sadat Hosseini et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…5 showed the swelling ability of the various lms. Initially, the large numbers of free hydroxyl groups in PVA lm absorbed water molecules and reached the maximum state of approximately 260% before reducing at 1.5 h. PVA/GT lms increased gradually and then remained at a steady rate of 250% due to the presence of hydrogen bonds in hydroxyl and carboxyl functional groups (Kurt, 2018). The porous structure of GT trapped water molecules (Khodaei et Stability of the wound dressing was assessed as the percentage weight loss of composite lm to indicate prolonged use (Zheng et al, 2019).…”
Section: Resultsmentioning
confidence: 99%